Non-Financial Reporting Research in Developed and Developing Countries - Muzammal Ahmad Khan; Jayakumar Chinnasamy (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2022)
Non-financial reporting is a disclosure of a company's social, environmental, and human rights information. It is also known as environmental, social, and governance information. This study attempts to assess the main content and future research suggestions reported in previous non-financial reporting studies and aims to offer recommendations for future research. Nine major databases over a decade (2005-2016) were explored using specific keywords, and 183 articles were identified to be exclusively dealt with non-financial reporting in both developed and developing nations. The finding indicates that there is a variation in the content focusing on non-financial reporting research in both developed and developing countries. Several selected articles have recommended that further research be focused on in-depth qualitative inquiries in the field to better support the practice of non-financial reporting.